2019
DOI: 10.7717/peerj.8099
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology and trophic ecology in a population of the polymorphic lizard Sceloporus minor (Squamata: Phrynosomatidae) from central Mexico

Abstract: Polymorphism among individuals of the same population has generally been linked to alternative reproductive tactics, where different morphs can exhibit differences in their morphological, ecological, and behavioral attributes. These differences may result in a divergence in diet between morphs due to differential exploitation of habitat, morphological differences that influence prey selection, or differential energy expenditure that results in different nutritional needs. The present study analyzes the morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(108 reference statements)
1
7
0
Order By: Relevance
“…In contrast, the possible function of polymorphic male dorsal coloration in S. minor remains unresolved (García-Rosales et al, 2017;Stephenson, 2010). Previous studies have argued that maintenance of the color polymorphism in this population is probably not due to niche partitioning (García-Rosales, Ramírez-Bautista, & Stephenson, 2019;García-Rosales et al, 2021); furthermore, in this study, we found no effect of the polymorphism on female choice or degree of male aggressiveness. Therefore, fieldbased studies of reproductive physiology and behavior are needed to evaluate the proportion of morphs over a longer period of time, since the polymorphism in this population could be explained by at least two hypotheses: (1) the morphs are maintained by their different reproductive qualities, and each morph is evolutionarily stable, or (2) the maintenance of these morphs at this site is due to frequency-dependent selection, where the fitness of a morph depends on the frequencies of the other morphs with which it competes (Pryke et al, 2007;Sinervo & Lively, 1996).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In contrast, the possible function of polymorphic male dorsal coloration in S. minor remains unresolved (García-Rosales et al, 2017;Stephenson, 2010). Previous studies have argued that maintenance of the color polymorphism in this population is probably not due to niche partitioning (García-Rosales, Ramírez-Bautista, & Stephenson, 2019;García-Rosales et al, 2021); furthermore, in this study, we found no effect of the polymorphism on female choice or degree of male aggressiveness. Therefore, fieldbased studies of reproductive physiology and behavior are needed to evaluate the proportion of morphs over a longer period of time, since the polymorphism in this population could be explained by at least two hypotheses: (1) the morphs are maintained by their different reproductive qualities, and each morph is evolutionarily stable, or (2) the maintenance of these morphs at this site is due to frequency-dependent selection, where the fitness of a morph depends on the frequencies of the other morphs with which it competes (Pryke et al, 2007;Sinervo & Lively, 1996).…”
Section: Discussionsupporting
confidence: 58%
“…For example, Bastiaans et al (2013) noted that in studies of lizards with discrete red or orange morphs, field experiments have found increased aggression in these color morphs as compared to others (Olsson et al, 2007;Sinervo & Lively, 1996), whereas studies conducted in the laboratory or semi-natural enclosures have found that individuals with orange coloration show a decrease in aggressiveness (Bastiaans et al, 2013). However, earlier work evaluating aggressive behavior of male S. minor in the field showed greater aggressiveness of the yellow morph as compared to the red morph (García-Rosales et al, 2021), in contrast to the pattern reported by Bastiaans et al (2013) in S. grammicus.…”
Section: Aggressive Behavior Between Malesmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding sexes, it has been observed that males generally show a higher frequency of tail loss compared to females, which has been related to the greater exposure of males during courtship and mating (García-de la Peña et al, 2004;García-Rosales & Martínez-Coronel, 2016;Leyte-Manrique et al, 2007). Furthermore, in some species of lizards, males are more colourful than females and are therefore more visible to predators (García-Rosales et al, 2021).…”
Section: Introductionmentioning
confidence: 99%